2012
DOI: 10.1037/a0030303
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of climate in clinical psychology doctoral programs: Development and initial validation of the Graduate Program Climate Scale.

Abstract: Measurement of program climate, defmed as a sense of environmental safety amid respectful relationships and effective organizational systems, has been associated with a myriad of important outcomes in school and workplace settings. However, climate has received scant attention in the realm of graduate training, including training in psychology health service programs, despite related research suggesting that quality of mentor-mentee relationships and the research training environment influences student satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…To measure participants’ perceptions of the climate in their graduate programs, we used a modified version of the Graduate Program Climate Scale (GPCS), which was originally developed by Veilleux et al. (2012), to address issues relevant to graduate programs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure participants’ perceptions of the climate in their graduate programs, we used a modified version of the Graduate Program Climate Scale (GPCS), which was originally developed by Veilleux et al. (2012), to address issues relevant to graduate programs.…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach’s α for the current study was 0.95, corresponding to excellent internal consistency. Prior studies have indicated this measure has acceptable internal consistency and concurrent validity (Veilleux et al. , 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Doctoral students may experience several sources of social support, from their faculty advisors to their peers to their friends and family (Clark et al. , 2009; Tompkins et al. , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Department climate, including environmental safety, and developing a culture of caring and respect, has been linked to doctoral student satisfaction (Anderson & Swazey, 1998;Brus, 2006;Protivnak & Foss, 2009;Veilleux, January, Vanderveen, Reddy, & Klonoff, 2012). It is possible that master's students' reduced time spent within a department could shield them from broader aspects of the department that can be problematic.…”
Section: Discussionmentioning
confidence: 99%